INFLUENCE OF FEEDING TIME ON FEED UTILIZATION BY SIAMESE CATFISH, Pangasius hypophthalmus JUVENILE - Nina Meilisza; Yann Moreau; Ettiene Baras; Rina Hirnawati (Indonesian Aquaculture Journal, 2010)
Siamese catfish (Pangasius hypophthalmus) at juvenile stage is used as ornamental fish by fish hobbies because of their beautiful shape and movement. Feeding time is a part of feeding management to get the best and effective strategy on feed input. This study aimed to determine the growth of Siamese catfish juvenile by looking at the influence of feeding time on feed utilization. The average individual weight of juveniles used was ± 3.2 g stocked 15 fish per aquarium equipped with recirculation system. Two level factors in the factorial design consisted of 4 feeding times (at 8:00, at 12:00, at 16:00, and as control (8:00, 12:00, 16:00) and feeding level (45 g feed kg-1 fish, 90 g feed kg-1 fish). Interaction between feeding time and feeding level resulting eight types of treatments research, namely A (8/45), B (12/45), C (16/45), D (8:12:16/45), E (8:12:16/90), F (8/90), G (12/90), and H (16/90). The results showed that feeding time had significant effect on the specific growth rate, feed conversion, and protein efficiency ratio and were significantly different among the treatments (P<0.05). Besides feeding time control (treatments D and E), treatment C also showed the highest of specific growth rate (2.03%), protein efficiency ratio (1.46), and the lowest feed conversion ratio (1.85).